Women Position Based on Interpetation of QS. At Taubah Verse 71, QS. An Nahl Verse 58-59, QS. Al-Isra’ Verse 70, and QS. Ali Imran Verse 195 - Zenudin, Nur Fadilah (International Conference of Moslem Society, 2019)
These verses explain about completing of law which is relating with struggle of seeking, deepening and applying knowledge. The goals from people who deepen religious knowledge are because of they want to guide all of Islamic people, teach them and give advice to them about the consequence of stupidity and not apply what they know. Hopefully, they will afraid to Allah SWT and do careful in all of bad things, beside into all of Islamic people understand in their religion and able to spread for all of people. From several verses, those explained that between man and woman should get the same education. Education is not just for man or woman only but for both (all of them). And in the class, there is nothing discrimination between man and woman. Woman has same position with man in education. It means that man and woman have same right and obligation in education.